(untitled) (Environment & Health, 2025)
The purpose of the study – determination of antibiotic sensitivity in pathogens of healthcare-associated infections isolated in Ukraine in 2023. Research materials and methods: The studied strains of microorganisms were received by the Reference Laboratory for the diagnosis of tuberculosis, bacterial, parasitic and especially dangerous pathogens of the State Institution "Center for Public Health of the Ministry of Health of Ukraine" from regional centers for disease control and prevention and health care institutions of Ukraine. Identification of microorganisms and determination of resistance were carried out using the VITEK 2 microbiological analyzer, MICTests trips and the WHONET computer program. Research results. In 2023, 1471 cultures of microorganisms were isolated and identified from wounds, blood, cerebrospinal fluid (CSF), urine and the external environment. The bacteria belonged to 9 species, namely: K.pneumoniae, E.coli, E.cloacae, P.aeruginosa, A.baumannii, S.aureus, S.epidermidis, E.faecium, S.haemolyticus. The largest number of bacterial strains, isolated from various biological materialis, were represented by K.pneumoniae, A.baumannii and P.aeruginosa. The pathogens S.aureus, S.epidermidis, E.faecium, S.haemolyticus were detected only in wounds and blood samples. Analysis of the results of determining the sensitivity of the isolated strains to antimicrobial drugs showed their high variability in the range from 100% to 27% and the need to determine the antibiogram for each isolate. Conclusions. 1. According to the results of the microbiological analysis, the sensitivity to antibiotics of pathogens of infections associated with the provision of medical care, which were isolated in Ukrainein 2023, was determined. Based on the results of the microbiological analysis, the sensitivity to antibiotics of pathogens of infections associated with the provision of medical care, which were isolated in Ukraine in 2023, was determined. 2. The largest number of strains of bacteria K.pneumoniae and A.baumannii and P.aeruginosa were isolated from all types of biological material. The pathogens S.aureus, S.epidermidis, E.faecium, S.haemolyticus were detected only in wounds and blood samples. 3. Analysis of the results of determining the sensitivity of the isolated strains to antimicrobial drugs showed their variability and the need to determine the antibiogram for each isolate. 4. A high level of resistance (90-100%) to penicillin, cephalosporin and aminoglycoside drugs was shown in the isolated strains of K. pneumoniae, E. coli, S.aureus, S.epidermidis, E.faecium, S.haemolyticus, P.aeruginosa. 5. A.baumannii strains were found to be insensitive to most of the tested antimicrobial drugs (88.9-100%). 6. Detection of S.aureus, A.baumannii, P.aeruginosa in the external environment may indicate the circulation of these resistant strains in health care facilities